(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Despite the untapped resource stored in ocean waves, none of the suggested wave energy converters (WECs) has yet demonstrated economical viability. This viability lies in two counter-productive aspects: enhancing energy absorption and generation, and reduction of the loads in the critical elements such as mooring lines and dynamic cables. Both objectives are counter-productive in the sense that the former implies enhancing the motion, while the latter requires reducing this motion. Hence, a trade-off between the two objectives must be found. To that end, the accurate lifetime estimation of the most critical components is crucial, which depends on the fatigue and extreme loads. The latter depends on extreme events, which are highly nonlinear and need to be characterised by fully-viscous fully nonlinear numerical models. In contrast, fatigue effects cause cracks in the material, which appear due to cyclic loading and, thus, computationally more efficient numerical models are required in order to study all the relevant loading conditions within the operating region. The present study will evaluate different methodologies to assess the impact of fatigue loads in WEC mooring lines, estimating the lifetime of the mooring lines under realistic wave climates. The method follows the following steps: • Mooring line tension is evaluated via hydrodynamic simulations under different realistic resource conditions, • Statistical characteristics of the load cycles are extracted from the time history, • The damage (D) corresponding to each load cycle condition is computed, • The lifetime (L) is estimated by combining realistic resource conditions and the damage corresponding to each condition In the present study, this approach will be applied to different mooring line configurations (including wire ropes and chains), materials (stud and studless) and dimensions (length and diameter of mooring lines), as shown in Figure 1 for stud and studless chains as a function of the diameter. The lifetime estimation will be performed in different locations across the European coast, analysing the impact of resource conditions on fatigue lifetime. In addition, the most relevant design parameters will be identified.